Prosodic Features of Short Dialogs in TOEFL ITP Listening Comprehension: Acoustic Phonetic Approach - Donal Fernado Lubis; Tri Arie Bowo (Journal of Language and Health, 2023)
Listening comprehension in Test of English as Foreign Language (TOEFL) has its own challenges, both in terms of listening and the comprehension process. This article explores aspects of prosody in short dialogues used in listening comprehension tests: duration, pitch, and intensities. The method applied in this research was descriptive qualitative with phonetic approach based on Collins and Mess’s Practical Phonetics and Phonology. A recording from ETS official website, consisting of thirty short dialogs were analyzed to perform the durations and pitch variations with the assistance of voice analyzer, Praat, especially for imaging process of pitch contour and measuring duration. Phonetic transcription showed the assimilation and elision processes occurred as the result of connected speech, while pitch variations tended to show more on attitudinal function, grammatical function, and fewer emphases on significant information. The voice actors performed the speech of General American accents naturally; however the nature of conversation itself would not be realized since this section is designed purposively to examine test-takers ability on semantic and pragmatic area. The duration of the speech is displayed as naturally as possible in the context of everyday conversation so that the perception of listeners who are not native speakers assesses it as rapid speech.